2005
DOI: 10.1128/jcm.43.9.4875-4876.2005
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Genes Encoding Staphylococcal Enterotoxins, Toxic Shock Syndrome Toxin 1, and Exfoliative Toxins in Members of the Staphylococcus sciuri Group

Abstract: Genes encoding staphylococcal enterotoxins (sea to see, seg, and seh), toxic shock syndrome toxin 1 (tst), and exfoliative toxins (eta and etb) were not detected in a large panel of 48 Staphylococcus sciuri group isolates tested. This strongly suggests that production of the staphylococcal exotoxins by these bacteria is highly unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…YPM may be associated with the particular scarlatinoid fever syndromes because it mediates an uncontrolled host immune system activation [20,54]. This is analogous to the role of superantigens in staphylococcal and streptococcal toxic shock syndromes [18,19]. The similarities in the clinical presentation of scarlet and scarlet-like fever suggest a direct role of YPM in the pathogenesis and the distinct clinical manifestation of Y.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…YPM may be associated with the particular scarlatinoid fever syndromes because it mediates an uncontrolled host immune system activation [20,54]. This is analogous to the role of superantigens in staphylococcal and streptococcal toxic shock syndromes [18,19]. The similarities in the clinical presentation of scarlet and scarlet-like fever suggest a direct role of YPM in the pathogenesis and the distinct clinical manifestation of Y.…”
Section: Resultsmentioning
confidence: 99%
“…In 1959, an epidemic of Y. pseudotuberculosis infections on the Pacific coast of Russia was called Far East scarlet-like fever (FESLF), or scarlatinoid fever [10–17] for its clinical similarities to scarlet fever caused by group A streptococci [18,19] . Such atypical infections in Far East Asia are severe, and the clinical presentation includes erythematous skin rash, skin desquamation, exanthema, hyperhemic tongue, and toxic shock syndrome [10,11,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The typical features of S. sciuri are coagulase negative, oxidase positive and novobiocin-resistant[33][35]. The isolate HBXX06 met these requirements.…”
Section: Discussionmentioning
confidence: 90%
“…It was also reported that one or more exfoliative toxins produced by isolates of S. hyicus from different countries could be detected [6]. Dakic and his colleagues examined the genes encoding staphylococcal enterotoxins (sea to see, seg, and seh), toxic shock syndrome toxin 1 (tst), and exfoliative toxins (eta and etb) in a panel of 48 Staphylococcus sciuri group isolates from animals and did not find any these genes [41]. In Another study, one hundred and twenty-one isolates from human and animals were examined for biofilm formation, hemagglutination, presence of clumping factor, production of spreading factors and exotoxins, cytotoxicity and capacity to stimulate nitric oxide production, and it was found that a wide spectrum of possible virulence determinants of S. sciuri existed [42], however their exact contribution to virulence of this bacterium in vivo remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Often, Y. pseudotuberculosis isolates from environmental and clinical sources harbor various plasmids ranging in size from 3-125 kb [7], some of which have been linked to pathogenicity [8,9]. In 1959, an epidemic of Y. pseudotuberculosis infections on the Pacific coast of Russia was called Far East scarlet-like fever (FESLF), or scarlatinoid fever [10][11][12][13][14][15][16][17] for its clinical similarities to scarlet fever caused by group A streptococci [18,19]. Such atypical infections in Far East Asia are severe, and the clinical presentation includes erythematous skin rash, skin desquamation, exanthema, hyperhemic tongue, and toxic shock syndrome [10,11,18,19].…”
Section: Introductionmentioning
confidence: 99%